NCOG-01. NEUROCOGNITIVE FUNCTION (NCF) AND QUALITY OF LIFE (QOL) RESULTS FROM A PHASE II STUDY OF TEMOZOLOMIDE-BASED CHEMORADIOTHERAPY REGIMEN FOR HIGH RISK LOW-GRADE GLIOMAS. (11th November 2019) - Wefel, Jeffrey; Pugh, Stephanie; Choucair, Ali; Fisher, Barbara; Fox, Sherry; Meyers, Christina; Ashby, Lynn; Mikkelsen, Tom; Glass, Jon; Yu, Michael; Howard, Steven; Movsas, Benjamin; et al.
Abstract: BACKGROUND: RTOG 0424 reported a 73.5% 3-year overall survival (OS) rate. This secondary analysis describes changes in NCF and QOL after therapy. METHODS: Patients with HR-LGG were treated with radiation and concurrent and adjuvant temozolomide. Standardized NCF tests were performed at baseline, 6 and 12 months (mos). Rates of NCF decline were examined using the reliable change index on Hopkins Verbal Learning Test (HVLT), Trail Making Test (TMT), and Controlled Oral Word Association. Relationships between NCF and subjective cognitive concerns (MOS-Cognitive Function [MOS-CF] scale) were evaluated with Wilcoxon Rank Sum Test. QOL was assessed using FACT-Brain. Longitudinal modeling using maximum likelihood estimation evaluated predictors of change in QOL. Cox models assessed the association of baseline NCF with OS after adjusting for age, anticonvulsants, number of high risk factors, EORTC OS risk group, and tumor crossing the midline. RESULTS: From 1/2005 to 8/2009, 129 evaluable patients were accrued, and 93 (72%) completed at least one NCF/QOL measurement with completers having better neurologic function than noncompleters (p=0.04). Compliance across measures was 55–59% and 54–57% at 6 and 12mos. Deterioration occurred in 50%/40% at 6mos/12mos, respectively, and was most frequent on HVLT (21%/20%), TMTA (29%/20%), and TMTB (22%/14%). Patients with HVLT deterioration at 12mos, compared to patients without deterioration, had significantly greater decrease in MOS-CF (p=0.01). No NCF test at baseline was independently associated with OS. FACT Emotional (p=0.02) and Functional Well-Being (p=0.004) subscales improved over time. EORTC OS high-risk group was associated with worse QOL on all subscales (p< 0.05 to 0.001) except Emotional Well-Being, tumor crossing the midline was associated with worse Emotional Well-Being (p=0.04), and unmethylated MGMT status was associated with better Physical Well-Being (p=0.05). CONCLUSIONS: Approximately half of patients with HR-LGG experience NCF decline in the first year after treatment with temozolomide-based concurrent chemoradiation. QOL remained stable or improved.